Methodology of synthesis of packing machines for food products based on multicriterial analysis - Kryvoplias-Volodina, Liudmyla; Gavva, Oleksandr M.; Derenivska, Anastasiia; Volodin, Oleksandr (My University, 2020)
The complex of technical means for optimization synthesis of assembling of a packing machine of separate functional modules has been developed. The method of synthesis of a packing machine, based on criterial assessment of separate functional modules (FM), combined by two main assessment groups, has been offered. FM may be selected and calculated by the program of consumption, based on the overall equipment effectiveness (OEE) criterion. An example of synthesis, based on the offered method, takes into account variants of choice of ready functional modules, based on the hierarchic structure of a module of roll packing material supply. The method takes into account the systemic approach to analysis of equipment constructions for packing fine-piece and piece food products in a consumption package. The synthesis of FM assembling as conceptual models, abstract ones, reflecting the construction structure and connections between separate elements – functional devices (FD) – has been offered. Розроблено комплекс технічних засобів оптимізації синтезу компонування пакувальної машини з окремих функціональних модулів. Запропоновано метод синтезу пакувальної машини на основі критеріальної оцінки окремих функціональних модулів (ФМ), об'єднаних двома основними групами оцінювання. ФМ може бути обраний і розрахований відповідно до загального критерію ефективності обладнання (ОЕЕ). Приклад синтезу, заснований на запропонованому методі, враховує варіанти вибору готових функціональних модулів, виходячи з ієрархічної структури модуля подачі рулонного пакувального матеріалу. Метод враховує системний підхід до аналізу конструкцій обладнання для упаковки сипких і штучних харчових продуктів в споживчу упаковку. Запропоновано синтез ФМ-збірки як концептуальних моделей, абстрактних, що відображають структуру конструкції та зв'язки між окремими елементами - функціональними пристроями (ФП).
Keywords: roll film material; functional module; generalized effectiveness criterion; рулонний плівковий матеріал; функціональний модуль; узагальнений критерій ефективності; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв